Distributional Laplace Transform of t^kF(t^r) - Panchal, Satish K (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this note distributional Laplace transform of the function t^k f (t^r) is obtained and the relation between the distributional one-sided Laplace trnsform of t^k f (t^r), r > 0, and the distributional Hankel transform of f (t^r) is established.